Characterization of putative DD-carboxypeptidase-interacting partners in mycobacterium smegmatis - Ralefeta, Ditshego Benjamin (My University, 2016)
Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), is responsible for the largest number of deaths due to a single bacterial pathogen. The persistence of TB in society is exacerbated by multiple factors, including the emergence of drug resistant forms of M. tuberculosis such as multi-, extensively- and totally-drug strains, which have fuelled a race for the discovery of new drugs with novel modes of action. However, the metabolic flexibility inherent in the tubercle bacillus has made the identification of vulnerable drug targets difficult. The peptidoglycan (PG) layer in the mycobacterial cell wall plays an essential role in bacterial growth, survival and antibiotic resistance but has not been exploited for TB drug development. In this study, we characterized the physiological function of mycobacterial DD-Carboxypeptidases (DD-CPases), a subgroup of Low Molecular Weight penicillin binding proteins (LMW PBPs), implicated in modulating the amount of PG cross-linking, thereby regulating the growth and remodelling of the PG polymer. Given that DD-CPases have not been characterized in actinobacteria, this study comprised the identification of M. smegmatis DD-CPases interacting partners, using the mycobacterial Protein Fragment complementation assay (mPFC), and interrogation of the functionality of the M. tuberculosis DD-CPase homologues through heterologous complementation in M. smegmatis. The Two DD-CPases, encoded by the MSMEG_2433 and MSMEG_6113 loci in M. smegmatis, were chosen for the identification of putative interacting partners. Screening of a genomic library using the mPFC assay identified 30 and 10 possible interacting partners for MSMEG_2433 and MSMEG_6113 respectively. Notably, some of these interacting partners included key regulators of cell elongation (PonA1) or division (PbpA and PbpB) and point to an important function for DD-CPases during mycobacterial growth. To further assess if genetic multiplicity for DD-CPases in M. tuberculosis is reflective of an underlying functional redundancy between these enzymes, the M. tuberculosis DD-CPase homologues (Rv2911, Rv3627c and Rv3330) were assessed for functionality through ectopic expression in M. smegmatis. The resulting heterologous M. smegmatis strains displayed altered colony morphology, with smooth colonies that displayed a mucoid surface and cording defects. Ectopic expression of the M. tuberculosis DD-CPases in M. smegmatis also resulted in aberrant biofilm formation and affected bacterial sliding on semi-solid agar, indicative of an alteration in the three-dimensional packing of cells in a community or changes in membrane properties. Over-expression of Rv2911 and Rv3627c resulted in reduced bacterial cell length accompanied by division defects. Transmission electron microscopy revealed that the M. tuberculosis DD-CPase homologues are involved in maintaining normal bacterial cell wall architecture. Over-expression of these homologues in native wild type M. tuberculosis H37RvS revealed a role for Rv3627c in regulating bacterial colony morphology. Cellular localization studies with rseGFP C-terminally tagged derivatives of these proteins revealed that they localize at the poles, mid-cell or and quartercell positions, further suggestive of a role in temporal and spatial co-ordination of cell growth and division. Collectively, the data point to important, possibly redundant roles for the multiple DD-CPases-encoding genes in M. tuberculosis and highlights these proteins as possible new drug targets for TB.
Dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine. June 2016